Influence of Ionizing Radiation and Hot Carrier Injection on Metal-Oxide-Semiconductor Transistors - Pejović, Momčilo; Osmokrović, Predrag; Pejović, Milica; Stanković, Koviljka (IntechOpen, 2012)
None